2004
DOI: 10.1021/la036261e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Hydrophobization on the Growth of Self-Assembled Monolayers on Silicon

Abstract: The growth of self-assembled monolayers from octadecyltrichlorosilane (OTS) on modified silicon surfaces has been investigated. The influence of different immersion times in a deactivation reagent on the growth mechanism and the ordering of the films has been studied. Characterization of the films and the submonolayer coverage has been performed with tapping mode atomic force microscopy, ellipsometry, and infrared spectroscopy. We found that a deactivation of active sites led to a higher mobility of adsorbed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…The theoretical length of fully extended OTS molecules in the all-trans conformation is 2.62 nm [26]. Also, several studies in the literature have previously reported that the islands with the height closer to 2.6 nm indicate that the hydrocarbon chains are oriented perpendicular to the surface [71,72]. Based on these observations, the OTS molecules in majority of these islands exhibit a vertical orientation on sp-Co-Cr alloy surface.…”
Section: Formation and Characterization Of Ots Sam On Co-cr Alloymentioning
confidence: 75%
“…The theoretical length of fully extended OTS molecules in the all-trans conformation is 2.62 nm [26]. Also, several studies in the literature have previously reported that the islands with the height closer to 2.6 nm indicate that the hydrocarbon chains are oriented perpendicular to the surface [71,72]. Based on these observations, the OTS molecules in majority of these islands exhibit a vertical orientation on sp-Co-Cr alloy surface.…”
Section: Formation and Characterization Of Ots Sam On Co-cr Alloymentioning
confidence: 75%
“…SAMs have been widely investigated in the past 20 years because of its potential applications in the field of surface modification, boundary lubricant, sensor, photoelectronics, and functional bio-membrane modeling, etc (Foisner et al, 2004;Gulino et al, 2004;Hsu, 2004;Love et al, 2005;Ostuni et al, 1999;Ulman, 1996;. On the basis of the surface chemical reaction and synthetic approaches, the chemical structures of SAMs can be manipulated easily at molecular level.…”
Section: One Component Samsmentioning
confidence: 99%
“…Recently, self-assembled nanofilms (SANFs), including self-assembled monolayers (SAMs), self-assembled multilayer films (SAMFs), self-assembled inorganic films (SAIFs) and selfassembled organic-inorganic composite films (SAO-ICFs), have generated substantial interest not only for its simple preparation procedure but also for its wide potential applications in many fields, such as surface modification, boundary lubricant coatings, sensors, photoelectronics, and functional bio-membrane modeling, etc (Foisner et al, 2004;Gulino et al, 2004;Hsu, 2004;Love et al, 2005;Ostuni et al, 1999;Ulman, 1996;. As a potential lubricant film for controlling stiction and friction in micro-/nano-electromechanical systems (MEMS/NEMS), SANFs offers distinct advantages over other strategies for lubrication of MEMS/NEMS devices.…”
Section: Introductionmentioning
confidence: 99%
“…To create such bactericidal surfaces, we have utilized organosilane covalent bonds to tether antibiotics and other biofactors to the surface of the implant [121,123]. The silane chemistry used during this process is well-characterized for various materials [124][125][126][127]. We have initially modified the chemistry of silanization to derivatize pure titanium and are currently applying similar methods to Ti6Al4V alloys [121,123].…”
Section: Selfprotective Smart Implantsmentioning
confidence: 99%